Risk assessment and reduction options for Ceratocystis platani in the EU. (22nd December 2016) - ,; Jeger, Michael; Bragard, Claude; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; Potting, Roel; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health (PLH) Panel performed a risk assessment for Ceratocystis platani in the EU with the aim to assess the effectiveness of risk reduction options (RROs) on the basis of the mechanisms of spread identified in the pest categorisation (natural and human‐assisted means, including waterways, root anastomosis, contaminated pruning tools, machinery, insects, contaminated insect frass and sawdust). C. platani is a destructive pathogen of Platanus trees, which is currently present in the EU (in France, Greece and Italy). Three scenarios were considered: the current situation (A0 scenario); the situation without RROs (A1 ); and the application of additional RROs (A2 ). The risk of new introductions into the EU of C. platani by means of the main pathways of entry (i.e. plants for planting, wood and machinery, e.g. construction machinery and pruning/cutting tools) is relatively limited, but about 250 times higher for the A1 scenario compared to the A2 scenario (median numbers of established populations). The risk of spread from already affected EU regions is higher, but varies depending on the scenario. Machinery is the most important mechanism of long‐distance spread. Focusing the additional RROs in A2 scenario on this mechanism of spread – which is not currently regulated – would be an effective way to reduce the likelihood of further spread and thus impacts of C. platani to not yet affected EU regions. The emergency measures applied by the C. platani ‐affected EU Member States (France, Greece and Italy) could be harmonised and improved. An enhanced programme could be developed which includes surveillance, early detection of the disease foci, effective eradication measures and planting resistant Platanus clones in new plantations in affected areas. Surveillance could also be intensified in the EU MSs not yet known to be affected by the disease.